Abdel- Karim Soroush’s views on understanding the religious text and religious knowledge - Kadhem, Yunes Jaafar (Journal of Islamic Sciences, 2020)
The research deals with the study of the opinions of contemporary Iranian thinker Dr. Abdul Karim Soroush in understanding the text Religion and religious knowledge, as the essence of what Soros went to is the distinction between the fixed and sacred religious text and the constantly changing and renewed religious understanding through an open reciprocal relationship generated by the text reader, according to this vision is dissolved Many contemporary intellectual problems in the field of religious understanding according to his claim, and the researcher reviewed the concepts of religion and religious knowledge of Sorush and the characteristics of each in his view and then outlined the contractual effects of this vision. The researcher concluded that accepting this vision leads to serious caveats, the most prominent of which is denying the authenticity of what Islamic scholars understood of religious texts and opening the way for the chaos of understanding the text and the spread of heresies and delusions on the pretext that religious knowledge is changing, changing and unholy. The researcher adopted from the descriptive and inductive approach and the critical approach as his ruler, in presenting the opinions of Dr. Abdel Karim Soroush and his views in his reading of the concepts of religion, religious knowledge, and then trying to analyze, discuss and criticize it.